Frequency of galactose-1-phosphate uridyl transferase gene mutations in healthy population of Croatia - Barišić, Karmela (Array, 2008)
Summary: Galactosemia is a human disease caused by deficient activity of each one of the three enzymes involved in galactose metabolism, galactokinase (GALK), galactose-1-phosphate uridyl transferase (GALT) and UDP-galactose-4-epimerase (GALE). Absence or deficiency of GALT activity results in classical galactosemia. This disorder exhibits allelic heterogeneity in different populations and ethnic groups. The aim of this study was to search for galactosemia mutations Q188R, N314D, and K285N in healthy population of Croatia. DNA samples from 221 subjects were analyzed by the polymerase chain reaction, followed by digestion with restriction endonucleases (PCR-RFLP procedure). Allele frequencies for Q188R, N314D, and K285N were found to be 0.2 %, 7.5 % and 0 %, respectively, and correlate well with those published for most other healthy Caucasian populations